The dose-effect of Tai Chi (Bafa Wubu) on mindfulness levels in college students: an 8-week randomized controlled trial - Li, Jiaqi; Chai, Qiuyue; Song, Anqi; Xiao, Yang; Zhang, Qiongyue; Lyu, Chengying; Zhao, Qiyue; Yin, Hengchan; Shen, Qiqi; Cui, Lei (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details